Hadith Delivery Method by Khatib During the Friday Prayer at Bandar Lampung Jami’ Mosque - Ikhwani, Ahmad; Zaki, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract The Prophet Muhammad’s hadiths are a type of revealed evidence (dalil naqli) that are often conveyed by khatibs in their sermons. As the most noble words after the Qur’an, hadiths must be delivered correctly and appropriately. Hadith scholars have established proper manners and procedures for delivering hadiths, such as the requirement to recite them fluently, adhere to the original text, translate and explain their meanings, and mention both the source and authenticity of the hadith. This study aims to examine the ways or methods used by Friday khatibs in delivering hadiths. The research was conducted on Friday khatibs at jami’ mosques located in the Bandar Lampung area. This is a field study. The researcher conducted surveys at several jami’ mosques in Bandar Lampung to observe and listen directly to how the khatibs deliver hadiths, including their fluency in reciting the hadith, accuracy in translating it, explanation based on correct understanding, and mention of the hadith’s source and authenticity. The evaluation criteria were rated on a scale of good, moderate, and poor. The research findings concluded that, in terms of fluency and translation, most khatibs were rated as good. However, in terms of understanding and explaining the hadith, only some khatibs received good ratings. As for mentioning the source and authenticity of the hadith, it was generally found to be very lacking. Keywords: Hadith; Jami’ Mosque; Khatib; Riwayat. Abstrak Hadis Nabi saw merupakan dalil naqli yang sering disampaikan para khatib dalam khotbahnya. Sebagai perkataan mulia setelah Alquran, hadis harus disampaikan secara baik dan benar. Ulama hadis sudah menyusun adab dan tata cara penyampaian hadis seperti harus fasih, sesuai teks asli, diterjemahkan dan dijelaskan maknanya, menyebutkan sumber dan kualitas hadis. Penelitian ini bertujuan untuk mengetahui cara atau metode khatib Jumat dalam penyampaian hadis. Penelitian dilakukan terhadap khatib Jumat di masjid-masjid jami’ yang terdapat di wilayah Kota Bandar Lampung. Penelitian ini adalah penelitian lapangan. Peneliti melakukan survey ke beberapa masjid jami’ di wilayah Kota Bandar Lampung untuk melihat dan menyimak langsung aktivitas penyampaian hadis oleh para khatib, meliputi kefasihan menyebutkan hadis, ketepatan menerjemahkan hadis, menjelaskan hadis berdasarkan pemahaman yang benar, penyebutan sumber periwayatan dan kualitas hadis. Standar penilaian tersebut akan diberi mutu atau skala penilaian baik, sedang, dan kurang. Hasil penelitian menyimpulkan, dalam hal kefasihan dan penerjemahan hadis para khatib umumnya sudah dinilai baik. Dalam hal pemahaman dan penjelasan hadis hanya sebagian khatib yang nilainya baik. Adapun berkaitan dengan penyebutan sumber riwayat dan kualitas hadis pada umumnya masih sangat kurang. Kata Kunci: Hadis; Khatib; Masjid jami’; Riwayat